2019
DOI: 10.3390/molecules24213872
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Novel µ-Opioid Receptor Inverse Agonist from a Combinatorial Library of Tetrapeptides through Structure-Based Virtual Screening

Abstract: Morphine, oxycodone, fentanyl, and other µ-opioid receptors (MOR) agonists have been used for decades in antinociceptive therapies. However, these drugs are associated with numerous side effects, such as euphoria, addiction, respiratory depression, and adverse gastrointestinal reactions, thus, circumventing these drawbacks is of extensive importance. With the aim of identifying novel peptide ligands endowed with MOR inhibitory activity, we developed a virtual screening protocol, including receptor-based pharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…On the other hand, both Goldscore and Chemscore were able to find a similar pose of tropolone superimposable to the crystallographic one with similar RMSD in the range of 2-3 angstorms. The best RMSD value self-docking of tropolone was obtained by using the Chemscore methods (RMSD = 2.33 Å), which was considerate good following the data reported in other works e.g., References [55,56]. The self docking also revealed that the best pose is similar to the crystallographic pose of tropolone cocrystallized to the tyrosinase-like 1 enzyme [57].…”
Section: Adme Estimationsupporting
confidence: 80%
“…On the other hand, both Goldscore and Chemscore were able to find a similar pose of tropolone superimposable to the crystallographic one with similar RMSD in the range of 2-3 angstorms. The best RMSD value self-docking of tropolone was obtained by using the Chemscore methods (RMSD = 2.33 Å), which was considerate good following the data reported in other works e.g., References [55,56]. The self docking also revealed that the best pose is similar to the crystallographic pose of tropolone cocrystallized to the tyrosinase-like 1 enzyme [57].…”
Section: Adme Estimationsupporting
confidence: 80%
“…An interesting study addressed by Poli et al (2019), used virtual screening as a method to filter the compounds with the greatest potential to be tested experimentally. Considered one of the first examples of virtual screening studies focused on the identification of new peptide ligands as opioid modulators, the authors used parallel virtual screening from an internal library.…”
Section: Different Molecular Docking Approaches Applied To Antinocicementioning
confidence: 99%
“…Structure-based drug design employs methods of receptor-based virtual screening (VS) and molecular docking for binding pose prediction, hit identification, and lead optimization. As part of our ongoing effort to discover new κ modulators with novel structures [ 40 ], the study herein is focused on the crystal structure of the KOR active-state for the discovery of novel KOR ligands using VS ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%